Thermodynamic study of solubility of B6 hydrochloride in water + co-solvent systems with UNIQUAC model at different temperatures - Hashemi, Seyed Hossein; Hosseini, Seyedeh Zahra (Journal of the Indian Chemical Society, 2022)
In this study, due to the importance of the solubility of this vitamin in solvents, based on the UNIQUAC activity coefficient equation, its solubility in the presence of water, acetonitrile, n-propanol and isopropanol has been studied. To investigate the interaction behavior of components in the system, the desired thermodynamic equations were optimized based on experimental results with a combined Genetic + PSO algorithm. Based on the objective function, the value of the theoretical and experimental model was acceptable. Therefore, the optimized model can be significant for formulating and investigating solubility of B6 hydrochloride based on the design of a computer program. [Display omitted]